Categories of Shifts in the Translation of the English Holy Bible (New International Version) into Dholuo Bible: Muma Maler Mar Nyasaye (1976) - Colleta Akoth Owino; Benard Mudogo; David Barasa; Rose Auma (Translation Studies: Theory and Practice, 2024)
This paper describes the categories of shifts in the translation of the English Holy Bible; New International Version (NIV) into Dholuo Bible Muma Maler mar Nyasaye (1976). The aim is to evaluate the relevance of the translator’s style in rendering a religious text into the target language and the overall implication on the translation theory and practice. The data is collected through document analysis and Focus Group Discussions. We analyzed forty rank shifted segments purposively from six books from the source and target text based on the Relevance Theory by Sperber & Wilson (1986). The analysis is limited to rank-shifting at the level of clauses utilized in the source language which is translated into the target language. The data is analyzed using content analysis and descriptive method. The following categories of shifts are identified; structure shifts, unit shifts, class shifts and intra-system shifts. This study offers insight to bible translators to understand that since shifts are unavoidable in translation, they should aim to produce a target text that is as accurate and precise as possible to guard against loss of meaning. To do this, translators must understand the original source text and transfer it faithfully and accurately. Moreover, bible translators must understand the context of both the source text and the target text since context plays a great role in rendering translation.